2019
DOI: 10.1002/acp.3584
|View full text |Cite
|
Sign up to set email alerts
|

Do secondary school students make use of effective study strategies when they study on their own?

Abstract: Although there is a large body of evidence for the utility of particular study strategies such as retrieval practice and distributed practice as memory-enhancing instruments, they are seldom used by learners in educational practice. Thus far, the research on the use of these study strategies has focused only on undergraduate university students, oftentimes only investigating a set of predefined strategies. The question, thus, remains whether these results are generalisable to secondary school students. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…For example, when reflecting on unsuccessful or negative outcomes, it is more adaptive to use explanations that center on strategy use (e.g., "I failed the test because I only reread the textbook and didn't create my own questions about the content") rather than one's ability level (e.g., "I failed the test because I am not smart enough").Adaptive self-beliefs, strategies, and self-evaluations can be taught and developed (e.g., van Alten et al, 2020). However, students likely do not develop these processes automatically or the ability to consistently and effectively apply them (Dirkx et al, 2019). SRL processes are often task-dependent and they differ based upon task features, including difficulty level (Cleary & Chen, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when reflecting on unsuccessful or negative outcomes, it is more adaptive to use explanations that center on strategy use (e.g., "I failed the test because I only reread the textbook and didn't create my own questions about the content") rather than one's ability level (e.g., "I failed the test because I am not smart enough").Adaptive self-beliefs, strategies, and self-evaluations can be taught and developed (e.g., van Alten et al, 2020). However, students likely do not develop these processes automatically or the ability to consistently and effectively apply them (Dirkx et al, 2019). SRL processes are often task-dependent and they differ based upon task features, including difficulty level (Cleary & Chen, 2009).…”
mentioning
confidence: 99%
“…Adaptive self-beliefs, strategies, and self-evaluations can be taught and developed (e.g., van Alten et al, 2020). However, students likely do not develop these processes automatically or the ability to consistently and effectively apply them (Dirkx et al, 2019). SRL processes are often task-dependent and they differ based upon task features, including difficulty level (Cleary & Chen, 2009).…”
mentioning
confidence: 99%
“…Even if students understand that different study behavior is necessary to benefit from FL, they do not always change their learning behavior, and they may even resist doing so (Boevé et al, 2017). In addition, research shows that students' knowledge about cognitive learning strategies is lacking, which in turn hampers metacognition during self-study, as students do not always use optimal learning strategies (Blasiman et al, 2017;Dirkx et al, 2019). On the one hand, this could be explained by the lack of sufficient training in effective study strategies such as distributed practice and retrieval practice (Dignath & Büttner, 2018;Surma et al, 2018).…”
Section: Higher Demand On Self-regulated Learning Skills In Flipped Lmentioning
confidence: 99%
“…Fourth, little research has been carried out to investigate the relationship between students' SRL activity and students' satisfaction. Research has shown that students struggle with effectively applying SRL during self-study (e.g., Blasiman et al, 2017;Dirkx et al, 2019). This can be related, for example, to their views on FL (Boevé et al, 2017), or to their appreciation of the SRL support (van Alten et al, 2020a).…”
Section: Self-regulated Learning Support In Online Flipped Learning Ementioning
confidence: 99%
See 1 more Smart Citation